Separate the variables:
![y' = (dy)/(dx) = (y+1)(y-2) \implies \frac1{(y+1)(y-2)} \, dy = dx](https://img.qammunity.org/2023/formulas/mathematics/college/1jjw99ounov136r50ia6h4fcfwigaf44hn.png)
Separate the left side into partial fractions. We want coefficients a and b such that
![\frac1{(y+1)(y-2)} = \frac a{y+1} + \frac b{y-2}](https://img.qammunity.org/2023/formulas/mathematics/college/uwcgwua9sa8dv87bmp8ui7n69b7mdqqozd.png)
![\implies \frac1{(y+1)(y-2)} = (a(y-2)+b(y+1))/((y+1)(y-2))](https://img.qammunity.org/2023/formulas/mathematics/college/prktkkeizvdoywcl5w6d7xsj82wphc1pr9.png)
![\implies 1 = a(y-2)+b(y+1)](https://img.qammunity.org/2023/formulas/mathematics/college/8f9kqitj8qar8cice6goisdesmzdv64kyz.png)
![\implies 1 = (a+b)y - 2a+b](https://img.qammunity.org/2023/formulas/mathematics/college/zn2gqh9sbapfq3tbw826ao83pf6se8eagm.png)
![\implies \begin{cases}a+b=0\\-2a+b=1\end{cases} \implies a = -\frac13 \text{ and } b = \frac13](https://img.qammunity.org/2023/formulas/mathematics/college/sqh2d8jv61dljasvaz81bro30ikcls5su8.png)
So we have
![\frac13 \left(\frac1{y-2} - \frac1{y+1}\right) \, dy = dx](https://img.qammunity.org/2023/formulas/mathematics/college/bojjuvi7377ybdez1sbi7vd1js9gbu7x05.png)
Integrating both sides yields
![\displaystyle \int \frac13 \left(\frac1{y-2} - \frac1{y+1}\right) \, dy = \int dx](https://img.qammunity.org/2023/formulas/mathematics/college/ocijntnrvxjyt90kd8yefvh4ewc16evbra.png)
![\frac13 \left(\ln|y-2| - \ln|y+1|\right) = x + C](https://img.qammunity.org/2023/formulas/mathematics/college/864n219af00244rr525gois0cxbdgcr52v.png)
![\frac13 \ln\left|(y-2)/(y+1)\right| = x + C](https://img.qammunity.org/2023/formulas/mathematics/college/78eagqtgn4ecm880yzi2j0cojyujmmdt3v.png)
![\ln\left|(y-2)/(y+1)\right| = 3x + C](https://img.qammunity.org/2023/formulas/mathematics/college/wn8jg30fkian4e4hkbd9atxkmfeq56juzt.png)
![(y-2)/(y+1) = e^(3x + C)](https://img.qammunity.org/2023/formulas/mathematics/college/oky5jfqzza3tlujph31buywq4div064bm9.png)
![(y-2)/(y+1) = Ce^(3x)](https://img.qammunity.org/2023/formulas/mathematics/college/u4aonazdsr8qa0k88ox0jfrn72nnyb8jky.png)
With the initial condition y(0) = 1, we find
![(1-2)/(1+1) = Ce^(0) \implies C = -\frac12](https://img.qammunity.org/2023/formulas/mathematics/college/h0o0k0difnqsvqir5uzlen4ju1cn93d2gg.png)
so that the particular solution is
![\boxed{(y-2)/(y+1) = -\frac12 e^(3x)}](https://img.qammunity.org/2023/formulas/mathematics/college/tv3b07l13q79eykhbl5kobrr7ww1g7rysb.png)
It's not too hard to solve explicitly for y; notice that
![(y-2)/(y+1) = ((y+1)-3)/(y+1) = 1-\frac3{y+1}](https://img.qammunity.org/2023/formulas/mathematics/college/s4byqxhapxa3p90yzqr050le13yp8puy56.png)
Then
![1 - \frac3{y+1} = -\frac12 e^(3x)](https://img.qammunity.org/2023/formulas/mathematics/college/qwpffc9mec0i8f5hi6dnq3ulscw3yfd594.png)
![\frac3{y+1} = 1 + \frac12 e^(3x)](https://img.qammunity.org/2023/formulas/mathematics/college/2dfg4myj717zlaisqy2l8hua7nphwrsh7d.png)
![\frac{y+1}3 = \frac1{1+\frac12 e^(3x)} = \frac2{2+e^(3x)}](https://img.qammunity.org/2023/formulas/mathematics/college/6x4wztqtsqklqu7yyff8v8mfb75us38yhr.png)
![y+1 = \frac6{2+e^(3x)}](https://img.qammunity.org/2023/formulas/mathematics/college/jzgread374i3ic6lcsj68pnpfa3pzfanax.png)
![y = \frac6{2+e^(3x)} - 1](https://img.qammunity.org/2023/formulas/mathematics/college/7ix7ujldn18lfxaxcq148f02ua8xrypfyk.png)
![\boxed{y = (4-e^(3x))/(2+e^(3x))}](https://img.qammunity.org/2023/formulas/mathematics/college/dhtvy09bk1ox7rqwgk6216olag4tnpcw2l.png)